Analisis Penerapan Metode Capital Asset Pricing Model (CAPM) dan Reward To Variability Ratio (RVAR) Dalam Pengambilan Keputusan Investasi Saham: Studi Kasus: Perusahaan-Perusahaan yang Terdaftar Pada Indeks LQ45 di BEI Periode Februari 2020 – Januari 2025 - Khaerunnisa, Winda; Santoso, Fahrul Imam (UMSurabaya Publishing, 2025)
The aim of this research is to analyze the grouping of stocks within the LQ45 index that can be considered in the construction of an investment portfolio using the Capital Asset Pricing Model (CAPM) and Reward to Variability Ratio (RVAR) methods. The CAPM method is used to measure the expected return of a stock based on its systematic risk. Furthermore, the RVAR method is applied to rank stock performance by comparing return levels with associated risk. This research employs a descriptive method with a quantitative approach. The data used includes monthly stock closing prices, IDX Composite as a market proxy, and the risk-free interest rate for the period from February 2020 to January 2025. The analysis results indicate that the top-performing stocks based on the combination of both methods, in order, are PT Alamtri Resources Indonesia Tbk (ADRO), PT Indo Tambangraya Megah Tbk (ITMG), PT Bukit Asam Tbk (PTBA), PT Aneka Tambang Tbk (ANTM), and PT United Tractors Tbk (UNTR).